2016
DOI: 10.1002/pon.4276
|View full text |Cite
|
Sign up to set email alerts
|

Japanese childhood cancer survivors' readiness for care as adults: a cross-sectional survey using the Transition Scales

Abstract: The results confirmed the reliability and validity of the Transition Scales and showed that Japanese CCSs expressed fewer cancer concerns, but a higher number of Japanese CCSs preferred to visit the same doctor for long-term care as adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…However, studies of the barriers to cancer survivorship faced by Chinese breast cancer patients revealed that survivors were wary of entrusting their complex health conditions to primary care physicians, whom they perceived to be poorly equipped to manage cancer-related health problems [ 121 ]. One study also reported that Japanese survivors of childhood cancer preferred to receive long-term care from the same physician as adults [ 122 ]. Supplement 4 summarizes the potential gaps and barriers to implementing a comprehensive survivorship program based on experiences from European and North American populations [ 113 , 120 , 123 , 124 ], as well as experience and existing interventions in the Asian population [ 26 , 125 133 ].…”
Section: Implications and Recommendations For Clinical Practicementioning
confidence: 99%
“…However, studies of the barriers to cancer survivorship faced by Chinese breast cancer patients revealed that survivors were wary of entrusting their complex health conditions to primary care physicians, whom they perceived to be poorly equipped to manage cancer-related health problems [ 121 ]. One study also reported that Japanese survivors of childhood cancer preferred to receive long-term care from the same physician as adults [ 122 ]. Supplement 4 summarizes the potential gaps and barriers to implementing a comprehensive survivorship program based on experiences from European and North American populations [ 113 , 120 , 123 , 124 ], as well as experience and existing interventions in the Asian population [ 26 , 125 133 ].…”
Section: Implications and Recommendations For Clinical Practicementioning
confidence: 99%
“…In particular, the effect size for the differences in the worry about job transfer between unemployed survivors with and without physical late effects was large. Japanese survivors of childhood cancer prefer not to see a doctor or nurse without their parents and to participate in making decisions about their health . Most of the unemployed survivors in the current study lived with parents (76% and 80% lived with their fathers and mothers, respectively).…”
Section: Discussionmentioning
confidence: 82%
“…Swiss survivors showed moderate cancer worries, with a higher CWS score than two Canadian cohorts [mean CWS score 62 (SD 19.88) versus 50.6 (SD 18.4) and 57.8 (SD 19.4)] ( 18 , 24 ). A Japanese study used the same CWS without reporting the score ( 19 ). The proportion of survivors that either agree or strongly agree to each of the six statements varies largely between the cohorts with Swiss survivors having the least cancer worries ( Supplemental Table 3B ).…”
Section: Discussionmentioning
confidence: 99%